火麻蛋白肽体内降血压功效研究Hypotensive effect in vivo of hemp protein peptides - 卫萍1,2，刘国明2,3，韦珍1，邓中霖1 WEI Ping1,2, LIU Guoming2,3, WEI Zhen1, DENG Zhonglin1 (Zhongguo youzhi)
旨在为火麻蛋白作为降血压功能因子提供基础理论依据，以火麻仁为原料，采用碱溶酸沉法制备火麻蛋白，再通过分步酶解法制备火麻蛋白肽，以火麻蛋白肽为原料进行动物实验探究其体内降血压功效。将大鼠分为正常对照组（Wistar雄性大鼠）、阳性组〔卡托普利20 mg/kg，雄性自发性高血压大鼠（SHR）〕、火麻蛋白肽中剂量组（750 mg/kg，雄性SHR）和火麻蛋白肽大剂量组（1 500 mg/kg，雄性SHR），研究短期给药（单日1次）和长期给药（连续21 d)对大鼠的尾动脉收缩压（SBP）、心律和体质量的影响，并对火麻蛋白肽的游离氨基酸组成进行分析。结果表明：卡托普利和火麻蛋白肽干预后，单日给药后1 h及连续给药7 d后均可显著降低SHR的收缩压，单日短期给药药效可持续5 h，长期给药21 d还有药效，且火麻蛋白肽大、中剂量组与阳性组相比，降压效果未见有显著差异（p>0.05）；短期给药和长期给药对SHR心率均有一定影响，而长期给药对SHR体质量没有显著影响（p>0.05）；火麻蛋白肽中与其发挥降血压功效相关的疏水性氨基酸占比高达3191%，此外，部分芳香族氨基酸（苯丙氨酸）、脂肪族氨基酸（亮氨酸、缬氨酸）以及碱性氨基酸（精氨酸和赖氨酸）含量也较高。综上，火麻蛋白肽在SHR体内具有一定的降血压功效，具有开发成新型降血压功能食品成分的潜力。In order to provide a theoretical basis for the use of hemp seed protein as a functional factor for lowering blood pressure, hemp seed protein was prepared by the alkali-soluble and acid-precipitation method with hemp kernel as materials, hemp protein peptides were prepared through a stepwise enzymatic hydrolysis process, and then hemp protein peptides were used as raw material to explore its hypotensive effect in vivo in terms of animal experiments. A normal control group (male Wistar rats), positive control group (captopril 20 mg/kg, male spontaneously hypertensive rats (SHR)), hemp protein peptides medium dose group (750 mg/kg, male SHR) and hemp protein peptides high dose group (1 500 mg/kg, male SHR) were set up to study the effect of short-term (once daily) and long-term (21 d consecutively) administration on the rat tail artery systolic blood pressure (SBP), heart rate and body weight. The free amino acid composition of hemp protein peptides was analyzed. The results showed that after adminstation with captopril and hemp protein peptides for 1 h of single day and 7 d of continuous administration, the SBP of the SHR could be significantly reduced, and the hypotensive effect of short-term administration and long-term administration could last for 5 h and 21 d, respectively. There was no significant hypotensive difference between medium/high dose group and captopril group （p>0.05）. Short-term and long-term administration both had a certain impact on the heart rate of SHR, while long-term administration did not significantly affect the body weight of SHR （p>0.05）. The proportion of hydrophobic amino acids in hemp protein peptides that are related to the effect of lowering blood pressure was as high as 31.91%. In addition, the contents of some aromatic amino acid(Phe), aliphatic amino acid(Leu and Val), basic amino acids (Arg and Lys) were also relatively high. In summary, the hemp protein peptides has a certain hypotensive effect in SHR, and is expected to be a new functional ingredient for lowering blood pressure.